Creation Dance Motion in Deaf Children to Develop Motor Balance in Anak Hebat Kindergarten Semarang - Widyoseptiani, Ariska; Ambari Sumanto, Reni Pawestuti (Jurusan PGPAUD FIP UNNES, 2021)
This study aims to determine the development of motor balance with deaf children's dance creation in Anak Hebat Kindergarten Semarang. This study uses a qualitative approach to the type of descriptive study. The data collected through interview techniques, observation, and data collection techniques (documents). The main informants in this study were 1 dance teacher and 2 class teachers, and the triangulation informants were 3 parents. The data analysis techniques used the theory of Milles and Huberman. The validity of the data uses the triangulation method. The results showed that dance motions for deaf children were repeated so that children could easily remember the motions. Dance motions that are taught can train children's motor balance such as jumping to the right and left with rotating arms and right and left legs raised one by one in turn, then there are circular motions by jumping with alternating legs, there are also tiptoe movements while the body bounces. These motions are motions that can train the balance of deaf children. There are two aspects, namely the creation of dance motions in deaf children and motor balance. Creation dance motion deaf children have a range of indicators of understanding of dance for deaf children, choreography forms of dance, characteristics of dance for children, the benefits of dance for deaf children. Motor balance also has a range of indicators namely understanding motor development, factors affecting motor development and elements of motor learning. The conclusion of this research is that dance learning is carried out continuously and motions that are easy and repetitive are important things that must be applied in dance learning for deaf children so that children easily understand and memorize. This study recommends that teachers should be even more varied in learning so that children do not get bored, in learning dance for deaf children, special techniques are reproduced again.